Perceived research burden of a novel therapeutic intervention: A study of transcranial magnetic stimulation for smoking cessation - Shevorykin, Alina; Carl, Ellen; Liskiewicz, Amylynn; Hanlon, Colleen A.; Bickel, Warren K.; Mahoney, Martin C.; Vantucci, Darian; Bensch, Lindsey; Thorner, Hannah; Marion, Matthew; Sheffer, Christine E. (Frontiers in Rehabilitation Sciences, 2023)
Background: Translating repetitive transcranial magnetic stimulation (rTMS) into evidence-based clinical applications relies on research volunteers with different perspectives on the burden of study participation. Additionally, clinical applications of rTMS require multiple visits over weeks or months, the impact of research burden is an important component for these studies and translation of these findings to clinical practice. High frequency rTMS has significant potential to be developed as an evidence-based treatment for smoking cessation, however, the optimal rTMS dosing strategies have yet to be determined. Participant burden is an important component of determining optimal dosing strategy for rTMS as a treatment for long-term smoking cessation. Methods: In this double-blinded, sham-controlled, randomized design, the effects of treatment duration, intensity, and active/sham assignment of rTMS on research burden were examined. Results: Overall level of perceived research burden was low. Experienced burden (M = 26.50) was significantly lower than anticipated burden (M = 34.12). Research burden did not vary by race or income. Conclusions: Overall research burden was relatively low. Contrary to our hypotheses, we found little evidence of added significant burden for increasing the duration or intensity of rTMS, and we found little evidence for differences in research burden by race or income.